2011
DOI: 10.1117/12.881645
|View full text |Cite
|
Sign up to set email alerts
|

Self-aligned triple patterning for continuous IC scaling to half-pitch 15nm

Abstract: A self-aligned triple patterning (SATP) process is proposed to extend 193nm immersion lithography to half-pitch 15nm patterning. SATP process combines lithography and spacer techniques in a different manner than the conventional selfaligned double patterning (SADP) by keeping the mandrel lines and the second spacers. Compared with other scaling candidates such as self-aligned quadruple patterning (SAQP), it can relax the overlay accuracy requirement of critical layers and reduce their process complexity by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…The 10T_BiDir cells are 10 tracks tall and have an acceptable active area efficiency of 66.67%, with restricted-2D M1 that is compatible with cost-effective patterning techniques such as self-aligned double patterning [11].…”
Section: ) 10t_bidir -Restricted Bidirectional-m1 Standard Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10T_BiDir cells are 10 tracks tall and have an acceptable active area efficiency of 66.67%, with restricted-2D M1 that is compatible with cost-effective patterning techniques such as self-aligned double patterning [11].…”
Section: ) 10t_bidir -Restricted Bidirectional-m1 Standard Cellmentioning
confidence: 99%
“…A structured grating has unequal line widths and equal spaces [16]. While structured 1D gratings are amenable to cost-effective patterning techniques such as self-aligned double patterning (SADP) [11] and directed self-assembly (DSA) [12], they also provide more design freedom than pure gratings (Section II.C.2). Nevertheless, 1D M1-based standard cells proposed earlier, while having favorable manufacturability, have been unsuccessful in meeting design requirements.…”
Section: ) 10t_unidir -Unidirectional-m1 Standard Cellmentioning
confidence: 99%
“…Plenty of research efforts have been devoted to TPL [4], [11], [18], [19], [22] [3], [13], [15]- [17]. Bei Yu et al showed that the general TPL decomposition problem is NP-hard, and further proposed an ILP based algorithm to compute legal TPL solutions [22].…”
Section: Introductionmentioning
confidence: 98%
“…Besides, it does not involve any stitch minimization. [13] [14] propose a self-aligned triple patterning (SATP) process to extend 193nm immersion lithography to half-pitch 15nm patterning. But the SATP process cannot insert any stitch, which would greatly constrain the possible layout patterns that are decomposable [15].…”
Section: Introductionmentioning
confidence: 99%